Systemic Responses of Barley to the 3-hydroxy-decanoyl-homoserine Lactone Producing Plant Beneficial Endophyte Acidovorax radicis N35 - Han, Shengcai; Li, Dan; Trost, Eva; Mayer, Klaus F.; Vlot, A. Corina; Heller, Werner; Schmid, Michael; Hartmann, Anton; Rothballer, Michael (Frontiers in Plant Science, 2016)
Quorum sensing auto-inducers of the N-acyl homoserine lactone (AHL) type produced by Gram-negative bacteria have different effects on plants including stimulation on root growth and/or priming or acquirement of systemic resistance in plants. In this communication the influence of AHL production of the plant growth promoting endophytic rhizosphere bacterium Acidovorax radicis N35 on barley seedlings was investigated. A. radicis N35 produces 3-hydroxy-C10-homoserine lactone (3-OH-C10-HSL) as the major AHL compound. To study the influence of this QS autoinducer on the interaction with barley, the araI-biosynthesis gene was deleted. The comparison of inoculation effects of the A. radicis N35 wild type and the araI mutant resulted in remarkable differences. While the N35 wild type colonized plant roots effectively in microcolonies, the araI mutant occurred at the root surface as single cells. Furthermore, in a mixed inoculum the wild type was much more prevalent in colonization than the araI mutant documenting that the araI mutation affected root colonization. Nevertheless, a significant plant growth promoting effect could be shown after inoculation of barley with the wild type and the araI mutant in soil after two months cultivation. While A. radicis N35 wild type showed only a very weak induction of early defense responses in plant RNA expression analysis, the araI mutant caused increased expression of flavonoid biosynthesis genes. This was corroborated by the accumulation of several flavonoid compounds such as saponarin and lutonarin in leaves of root inoculated barley seedlings. Thus, although the exact role of the flavonoids in this plant response is not clear yet, it can be concluded, that the synthesis of AHLs by A. radicis has implications on the perception by the host plant barley and thereby contributes to the establishment and function of the bacteria-plant interaction.